Smoking Knowledge, Attitude, and Practices among Health Care Professionals from Sulaymaniyah City/Iraq - Darya Saeed Abdulateef; Azheen Jamil Ali; Darwn Saeed Abdulateef; M.I. Glad Mohesh (SAGE Publishing, 2016)
Background Smoking is a serious risk to health globally. Health care professionals play a key role in the prevention of smoking as they are considered a role model by patients. Objectives The aims of this study are to evaluate smoking rate among physicians and dentists from Sulaymaniyah, Iraqi Kurdistan, Iraq, and to understand their knowledge and attitudes toward tobacco smoking. Methods A cross-sectional web-based survey was conducted involving physicians and dentists working in both University of Sulaimani and Sulaymaniyah Teaching Hospitals. A questionnaire created based on World Health Organization Global Health Professional Survey with slight modifications was emailed to the study participants and the responses received were analyzed. Results Incidence of smoking among physicians and dentists was 26.5%, with a significantly higher rate among male compared to female health care professionals. The mean age of starting smoking was 22.3 (±4.8) years. Only 7.3% of health care professionals received formal training on smoking cessation. All responders agreed that smoking is harmful to health. However, ever smokers compared to never smokers were less likely to agree that health care professionals should set a positive impact by not smoking. Conclusion Smoking rate is high among physicians and dentists from Sulaymaniyah city/Iraq, and at the same time, there is a low rate of training on smoking cessation.